BIOACUMULAÇÃO DE METAIS E MUTAGENICIDADE EM PEIXES COMO INDICADORES DA INTEGRIDADE AMBIENTAL NO RIO AMAMBAI-MS. - VIANA, Lucilene Finoto; SÚAREZ, Yzel Rondon; CARDOSO, Claudia Andrea Lima; CRISPIM, Bruno do Amaral; GRISOLIA, Alexeia Barufatti; LIMA-JUNIOR, Sidnei Eduardo (ANAIS DO ENIC, 2017)
-